Guiding Preschool Play for Cultural Learning: Preschool Design as Cultural Niche Construction - Samuelsson, Robin (Frontiers in Psychology, 2020)
This paper explores how preschools can be purposefully designed to aid cultural learning through guided play practices. In recent literature, there has been a renowned interest in the role of the exogenous environment in psychological processes, including learning. The idea that the design of preschools can meaningfully be seen as cultural niche construction and that guided play practices in these environments can aid the preparation for cultural action, is promoted, and a theoretical framework is presented. The empirical data draw from a synthesis from three ethnographic research sites in multilingual communities, and data are used to explore how cultural affordances are used in designed environments as part of guided play practices. The results indicate how niche construction of affordances aid cultural learning and is achieved through both direct guided play interaction between teachers and children, but also in the way of the indirect design of environments that is incorporated in children’s peer play. It is discussed what this means for play research as well as for guided play practices that aim to promote cultural learning.